Pharmacokinetic behaviour and pharmacokinetic–pharmacodynamic integration of doxycycline in rainbow trout (Oncorhynchus mykiss) after intravascular, intramuscular and oral administrations - Altan, Feray; Corum, Orhan; Durna Corum, Duygu; Uney, Kamil; Terzi, Ertugrul; Bilen, Soner; Sonmez, Adem Yavuz; Elmas, Muammer (Wiley, 2024)
AbstractObjectiveDoxycycline (DO) has been used in fish for a long time, but there are some factors that have not yet been clarified regarding its pharmacokinetic (PK) and pharmacodynamic (PD) properties. Therefore, the aim of this study was to investigate the PK and PK/PD targets of DO after 20 mg/kg intravascular (IV), intramuscular (IM) and oral (OR) gavage administration in rainbow trout (Oncorhynchus mykiss).MethodsPlasma samples were collected at specific time points and subsequently analysed by HPLC‐ultraviolet. The PK/PD indices were calculated based on the MIC90 (Aeromonas hydrophila and Aeromonas sobria) values obtained for the respective bacteria and the PK parameters obtained for DO following both IM and OR administration.ResultsAfter IV administration, the elimination half‐life (t1/2ʎz), area under the concentration vs. time curve (AUC), apparent volume of distribution at steady‐state and total body clearance of DO were 34.81 h, 723.82 h µg/mL, 1.24 L/kg and 0.03 L/kg/h, respectively. The t1/2λz of the DO was found to be 37.39 and 39.78 h after IM, and OR administration, respectively. The bioavailability was calculated 57.02% and 32.29%, respectively, after IM and OR administration. The MIC90 of DO against A. hydrophila and A. sobria was 4 µg/mL. The PK/PD integration showed that DO (20 mg/kg dose) for A. hydrophila and A. sobria with MIC90 ≤4 µg/mL achieved target AUC/MIC value after IM administration.ConclusionsThese results suggest that when rainbow trout was treated with 20 mg/kg IV and IM administered DO, therapeutically effective concentrations were reached in the control of infections caused by A. hydrophila and A. sobria.
Keywords: PK-PD integration; doxycycline; Veterinary medicine; Administration, Oral; Biological Availability; rainbow trout; Aeromonas hydrophila; Aeromonas sobria; FISH; Doxycycline; Oncorhynchus mykiss; SF600-1100; PK–PD integration; Animals; pharmacokinetics; 6. Clean water; 3. Good health; 14. Life underwater